2002
DOI: 10.1046/j.1365-2249.2002.01720.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced neutropenia associated with anti-neutrophil cytoplasmic antibodies (ANCA): possible involvement of complement in granulocyte cytotoxicity

Abstract: SUMMARY Although antineutrophil antibodies are thought to be involved in drug‐induced neutropenia, neither the precise mechanisms nor the particular antigens on the neutrophil surface have yet been clarified. Recently, we examined a patient with Graves’ disease who developed antineutrophil cytoplasmic antibodies (ANCA) after propylthiouracil treatment and exhibited neutropenia. Because several target antigens of ANCA are expressed on the surface of neutrophils, it was suggested that ANCA might contribute to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 32 publications
2
26
0
1
Order By: Relevance
“…This data suggests an immune-mediated mechanism rather than direct toxic effects of the drug, but the precise mechanisms have not been clarified (3,18). Several studies have reported that antineutrophil cytoplasm antibodies (ANCA) might contribute to propylthiouracil-(PTU) induced agranulocytosis but these have not been observed in MMI therapy (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests an immune-mediated mechanism rather than direct toxic effects of the drug, but the precise mechanisms have not been clarified (3,18). Several studies have reported that antineutrophil cytoplasm antibodies (ANCA) might contribute to propylthiouracil-(PTU) induced agranulocytosis but these have not been observed in MMI therapy (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…PTU-induced autoimmune disease was known as PTU-induced lupus-like syndrome, PTU is also known as a trigger for antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis. Recently, complement-mediated cytotoxicity was postulated as a mechanism of PTU-induced ANCA-positive neutropenia [9]. ANCA specific for proteinase 3 (PR3) and myeloperoxidase (MPO) are associated with necrotizing vasculitis, and ANCA-activated neutrophils contribute to oxidative and proteolytic damage of blood vessels [10].…”
Section: Discussionmentioning
confidence: 99%
“…ANCA specific for proteinase 3 (PR3) and myeloperoxidase (MPO) are associated with necrotizing vasculitis, and ANCA-activated neutrophils contribute to oxidative and proteolytic damage of blood vessels [10]. Priming (TNF-alpha)-induced translocation of PR3 and MPO to the cell surface may induce cytotoxicity [9]. ANCA-associated vasculitis and ATD-associated ANCA-positive patients in Belgrade were reported [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may affect the microenvironment of bone marrow and inhibit the generation and differentiation of pluripotent hematopoietic stem cells. The immunological reactions include the immunoglobulin (Ig) E-mediated hypersensitivity reaction, drug-induced IgG and IgM responses, and antineutrophil cytoplasm antibodies (ANCA) associated immune injury, which might contribute to agranulocytosis [1,7,[12][13]. Bone marrow characteristics may be valuable in revealing the tion of the 33 cases, there were 15 cases with bone marrow active proliferation, 3 cases with hyperplasia and 2 cases with hypoplasia in type I, while 3 cases with hyperplasia and 10 cases with active proliferation were indentified in type II.…”
Section: General Conditionmentioning
confidence: 99%
“…Therefore, hypoplasia with decreased or absent of precursor cells is the common characteristics of drug toxicity [10]. However, ATD related immune complexes may selectively react on antigen targets on the surface of mature granulocytes or granulocyte progenitor cells [6,12]. The hematopoietic function of bone marrow is not completely inhibited.…”
Section: Clinical Characteristicsmentioning
confidence: 99%